PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS KELAS IV - Puspita, Laudya Ino; Taufik, Mirna; Sugiarti, Sugiarti (Universitas Negeri Medan, 2024)
Abstract: This research aims to determine the development of student worksheet products (LKPD) using problem based learning models based on local wisdom in class IV science subjects that are valid and practical. The method used in this research is research and development, with a 4D development model consisting of (Define, Design, Development and Disseminate). The subjects of this research were class IV students at SD Negeri 92 Palembang. The results of the validity test of this research obtained a score of 83.5% which was categorized as